THE IMPACT OF OVERCONFIDENCE BIAS ON PERSONAL INVESTMENT DECISIONS: THE CASE OF NORTH MACEDONIA - Hadzimustafa, Shenaj; Shabani, Nermine (Faculty of Economics - Skopje, Ss Cyril and Methodius University, 2020)
The "Financial Behavior" in the field of "decision making" is the topic that awarded the economist Richard H. Thaler the Nobel Prize in 2017. According to him, after many investigations made on human decisions, it is noticed that they often depend on nature, intuition, habits, cognitive biases, emotional biases which lead the investor to wrong decisions. Given that the investments play an important and central role in the economy, the main purpose of the paper is to analyze the investment decision making process based on emotional bias, or more specifically the overconfidence bias. This study captures the impact of gender, and level of education on overconfidence during investment decision making in North Macedonia. The results show that investors' decisions were significantly influenced by the overconfidence bias. Although men and women are found to be overconfident, studies have shown that the degree of overconfidence varies among them and men are more overconfident than women. Also, overconfidence increases with the level of education. Based on the results certain recommendations are provided in order to assist future investment decision-making processes by notifying and eliminating the overconfidence bias identified during this research as a key factor leading to wrong and failing, non-rational investment decision making.
Keywords: Behavioral Finance; Biases; Investment Decision; Investors; Overconfidence